Evaluation of stainless steel pipe performance as a ground heat exchanger in ground-source heat-pump system. (15th October 2016) - Yoon, Seok; Lee, Seung-Rae; Kim, Min-Jun; Kim, Woo-Jin; Kim, Geon-Young; Kim, Kyungsu
Abstract: This paper presents a numerical and experimental study of the evaluation of stainless steel (STS) pipe performance as a ground heat exchanger (GHE). U-type GHEs of circular polybutylene (PB) and annular STS were installed in a steel box (5 m × 1 m × 1 m), and indoor thermal response tests (TRTs) were conducted for 30 h to evaluate the heat-exchange rates. The U-type GHEs of PB, annular STS, and indoor TRT conditions were numerically modeled using a three-dimensional finite-element method. The average pipe diameter for the annular STS pipe was determined by the finite-element method. The exchange rate of the annular STS pipe was approximately 10% higher than that of the circular PB pipe, and the temperature distributions measured in the TRT and calculated by the numerical analysis exhibited reasonable agreement. In addition, the borehole thermal resistance and heat-exchange rate under the assumption that the annular STS pipe would be applied in an actual vertical heat exchanger system were calculated. It is expected that the borehole thermal resistance would be decreased by 25% and that the heat-exchange rate would be increased by 15% with annular STS pipe in comparison with PB pipe. Highlights: An annular STS pipe was used as a GHE. In-door thermal response tests were conducted to evaluate heat exchange rate. Numerical analysis was conducted to predict measured experimental results. Application of STS pipe to a GSHP system was suggested.